Microbiological and biochemical changes in Thua nao fermentation - Chukeatirote E. (2014)
In this study, we aimed to investigate the microbiological and biochemical changes during the fermentation. It was showed that microbial population (bacteria and fungi) and pH increased with fermentation time. The bacterial groups isolated were further characterised and found to be Bacillus sp.; however, some Lactobacillus sp. and unidentified cocci were also detected. In addition, some chemical properties (i.e., pH and ammonia concentration) and enzymatic activities were determined. Proteases and amylases activities increased rapidly reaching a peak at 60 h (100% relative activity) and at 72 h (1,380 U), respectively. Phytase activity was also detected varying from 114.7-152.6 U. In contrast, lipases activity was minimal throughout the fermentation (0.78-1.31 U). © 2010 Academic Journals Inc.